The chromosome-level genome assembly of lance asiabell (Codonopsis lanceolata), a medicinal and vegetable plant of the Campanulaceae family - Jang, Woojong; Kang, Ji-Nam; Jo, Ick-Hyun; Lee, Si-Myung; Park, Gyu-Hwang; Kim, Chang-Kug (Frontiers in Genetics, 2023)
Codonopsis lanceolata (2n = 2x = 16) belongs to the Campanulaceae family and is a valuable medicinal and vegetable plant primarily found in East Asia. Several studies have demonstrated its excellent pharmacological effects, for example in bronchial treatment. However, genomic information of C. lanceolata is scarce, hindering studies on crop improvement of the species. Here, we report a high-quality chromosome-level genome assembly of C. lanceolata based on a hybrid method using Nanopore long-read, Illumina short-read, and Hi-C data. The assembled genome was completed as 1,273 Mb (84.5% of the estimated genome size), containing eight pseudo-chromosomes, ranging from 101.3 to 184.3 Mb. The genome comprised of 71.3% repeat sequences and 46,005 protein-coding genes, of which 85.7% genes were functionally annotated. Completeness of the assembled genome and genes was assessed to be 97.5% and 90.4%, respectively, by Benchmarking Universal Single-Copy Orthologs analysis. Phylogenetic and synteny analysis revealed that C. lanceolata was closely related to Platycodon grandiflorus in the Campanulaceae family. Gene family evolution revealed significant expansion of related genes involved in saponin biosynthesis in the C. lanceolata genome. This is the first reference genome reported for C. lanceolata. The genomic data produced in this study will provide essential information for further research to improve this medicinal plant and will broaden the understanding of the Campanulaceae family.